PERFORMANCE AND YIELD OF COWPEA (VIGNA UNGUICULATA L. WALP) SUBJECTED TO IMPOSED WATER DEFICIT - AKINYEMIJU, O. A.; FAPOHUNDA, H. O.; ADEGOROYE, A. S. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Growth performance, yield and yield component analysis studies of water-stressed irrigated cowpeas were conducted using cowpea cultivars: Ife Brown and TVx 3236 in order to determine the best phenological stage to stop irrigation. Water stress was imposed by stopping irrigation at seedling establishment. 50% vegetative growth, first flowering, 50% flowering, pod setting or 50% pod fill. The effect of cultivar was not significant in all parameters evaluated. Cowpea seed yield progressively increased from 7 g/plant for plants that received 80-160 mm of water during the seedling establishment and early vegetative growth stages to 11-22 g/plant for crops that received 260-320 mm of water from planting till end of vegetative and early flowering stages. Seed yield was only 24-26 g/plant for cowpea irrigated from planting till end of flowering and pod filling stages. The phenological stage to stop irrigation and still obtain high yield in irrigated cowpea was at the end of the flowering stage. Irrigating beyond this stage increased total biomass but reduced seed yield by about 8 percent.